PENGARUH KETERAMPILAN, PENGETAHUAN, KONSEP DIRI DAN NILAI-NILAI, DAN KARAKTERISTIK PRIBADI TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN ORGANISASI PADA DISHUBKOMINFO KAB. BANYUMAS - Pipin Widyasari (Multiplier: Jurnal Magister Manajemen, 2017)
To realize vision and mission of Dishubkominfo Banyumas District one of them are to increase public services in traffic and public transportation. So, Dishubkominfo Banyumas District continues to work to improve the quality of to empower all of the employee so that it will have strong performance and can work with optimally, effective, and efficient. The aims of the research are 1) to describe skills, knowledge, concept of self and values, personal characteristic, organization, commitment, and performance; 2) to describe the influence of skill, knowledge, concept of self and values, and personal characteristic to organization commitment; 3) describe the influence of skills, knowledge, concept of self and values, and personal characteristic to performance; 4) describe the influence of organization commitment to employees performance; 5) describe the influence of skill, knowledge, concept of self and values, and personal characteristic to employees performance through organization commitment. Respondent of this research are 100 people. The respondent are the employees of Dishubkominfo Banyumas District. This research using Structural Equation Modeling (SEM) which do by AMOS 4.00 as the instrument of analysis. The result of this research prove that fourth coefficient can be conclude that variable concept of self and values more influence to variable organization commitment, compared with skill variable, knowledge variable, and personal characteristic variable. It can be prove with significantly value of p-value is very small (0,001), so the hypothesis which said there is an influence between variable of skill, knowledge, concept of self and values, personal to variable of organization commitment is attested. From that coefficient it can be conclude that concept of self and values variables is more influence to performance variable compared with the other variable.it can be prove with significantly value of p-value on table column O on output program Amos Ver 19, so the p-values is very small (0,001). Therefore, the hypothesis which said there is an influence between variable of skill, knowledge, concept of self and values, and personal characteristic to performance variable on DishubkominfoBanyumas District is attested. Significantly values of p-value on table column P and the output of Amos Program Ver 19, so the p-value is very small (<0,001), so the hypothesis which said there is an influence between organization commitment to performance of Dishubkominfo Banyumas District is attested. Significantly values of p-value on table column O on output program of Amos Ver 19 which means the value of p-value is very small (<0,001), so the hypothesis which said there is an influence between skill, knowledge, concept of self and values, and personal characteristic to performance through organization commitment on Dishubkominfo Banyumas District is attested. Â Keywords: skill, knowledge, concept of self and values, personal characteristic, performance, organization commitment.